2014
DOI: 10.5812/numonthly.23563
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Plasma Beta-2 Microglobulin Level and Cardiac Performance in Patients With Chronic Kidney Disease

Abstract: Background:Beta-2 microglobulin (B2M) is considered as a surrogate marker for middle molecule uremic toxins and a key component in dialysis-related amyloidosis. However, few studies have evaluated role of B2M in patients with chronic kidney disease (CKD).Objectives:The purpose of this study was to evaluate the association of plasma B2M level with some metabolic and cardiac performance factors in patients with CKD.Patients and Methods:In this case-control study, we measured plasma B2M level in 86 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…Nevertheless, the association between serum B2M and MIA syndrome had not been well investigated. As previous studies, B2M was associated with stroke, cardiac performance, and CVEs . Besides, B2M was also associated with inflammation , which played an important role in pathophysiology of MIA syndrome .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Nevertheless, the association between serum B2M and MIA syndrome had not been well investigated. As previous studies, B2M was associated with stroke, cardiac performance, and CVEs . Besides, B2M was also associated with inflammation , which played an important role in pathophysiology of MIA syndrome .…”
Section: Discussionsupporting
confidence: 74%
“…Elevated B2M had been observed in malignancy, renal, immunodeficiency, and autoimmune disease (8)(9)(10). B2M was associated with cardiac performance and mortality in those with CKD and those on maintenance hemodialysis (11)(12)(13). It was also a thrombotic marker for peripheral artery occlusive disease (14).…”
Section: Introductionmentioning
confidence: 99%
“…In our study cohort, increased levels of β2M demonstrated prediction for early diagnosis of CIN and were associated with increased mortality. Several studies on β 2 M have focused on populations with underlying CKD [13]. In a study limited to a paediatric population, El-Frargy et al found significantly increased levels of baseline β 2 M in AKI patients compared to controls; however, the levels of serum creatinine remained unchanged [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, in the presence of renal disease including CIN, the impact of high β 2 M levels is heightened [40]. Other possible reasons include that β 2 M is a filtration biomarker produced by nucleated cells [13], which undergoes almost complete metabolism in the kidney. It is completely absorbed by megalinmediated endocytosis [13,27] and is also least affected by extra renal factors [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation